The change of Cr and Mn concentrations in selected plants in Samsun city center depending on traffic density - Karacocuk, Tugba; Sevik, Hakan; Isinkaralar, Kaan; Turkyilmaz, Aydın; Cetin, Mehmet (Landscape and ecological engineering, 2022)
In recent years, air pollution has increased significantly due to anthropogenic factors and has become a global problem. Heavy metals in air pollution components; it is of particular importance because they are not easily degraded and disappeared in nature, bioaccumulation in living bodies, some of them can be toxic, toxic or carcinogenic even at low concentrations and even those necessary for living bodies can be harmful at high concentrations. Therefore, monitoring the concentrations of heavy metals in the air is of great importance for human and environmental health. Biomonitoring is the most suitable method for monitoring the concentration of heavy metals. Plants that can accumulate heavy metals in different organs are suitable biomonitors. However, the most appropriate type and organ for monitoring each heavy metal must be determined separately. In this study, the changes in the concentrations of the elements Cr and Mn in Robinia pseudoacacia, Platanus orientalis, Acer negundo, Ulmus minor and Nerium oleander species were determined by the individuals who grow in areas where there is no traffic, less and dense. The Cr and Mn concentrations in the leaves, bark and wood of the species subject to the study were evaluated. Within the scope of the study, the washing process was also applied to the leaves and shells and the effect of the washing process was tried to be determined. As a result of the study, it was determined that the concentrations of each element in different species vary depending on the traffic density and this change can vary greatly on the basis of element and species.